Razporeditev prebivalstva v Severovzhodni Sloveniji z vidika kraja bivanja in kraja zaposlitve (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1991)
The article analyses the relation between the number of active population in a dweeling and working place and relation of the employed concerning the working place with the purpose of finding out the degree of demogeographic mobility.
Keywords: demogeografija; geografija; geography